Happiness from Ordinary and Extraordinary Experiences - Bhattacharjee, Amit; Mogilner, Cassie (Journal of Consumer Research, 2014)
Abstract Prior research indicates that experiences bring greater happiness than material possessions, but which experiences result in the greatest happiness? The current investigation is one of the first to categorize types of experiences and highlights one important distinction: the extent to which an experience is ordinary (common and frequent) versus extraordinary (uncommon and infrequent). Eight studies examine the experiences individuals recall, plan, imagine, and post on Facebook finding that the happiness enjoyed from ordinary and extraordinary experiences depends on age. Younger people, who view their future as extensive, gain more happiness from extraordinary experiences; however, ordinary experiences become increasingly associated with happiness as people get older, such that they produce as much happiness as extraordinary experiences when individuals have limited time remaining. Self-definition drives these effects: although extraordinary experiences are self-defining throughout one's life span, as people get older they increasingly define themselves by the ordinary experiences that comprise their daily lives.